Pengaruh Tiktok Marketing Ecinos Terhadap Brand Awareness dan Brand Image pada Followers Tiktok @ecinos.id - Monica Febriana; Trimanah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research is motivated by the growing popularity of TikTok as a digital platform used by brands to increase brand awareness and image. Ecinos.id is a local brand that utilizes TikTok marketing strategies to build rapport with its audience and strengthen its market position.fashion.This study aims to determine how much influence TikTok marketing has onbrand awareness And brand image on followers TikTok @ecinos.id. The theory used in this study isBrand Equity Theory The type of research conducted is quantitative explanatory using the paradigmpositivism. Data collection is done using techniques probability sampling to 100 respondents who were followers of TikTok @ecinos.id. The calculation test in this study used simple linear regression analysis with the help of IBM SPSS Version 27 to test the statistical data. The results of the validity and reliability tests for all questionnaire items showed that all items were valid and reliable. The results of the simple linear regression analysis showed a significant influence of TikTok marketing on brand awarenessas big as 44,4%, while the rest 55,6%influenced by other factors not studied. TikTok marketing also has a significant influence on brand imageas big as 38,8%, while the rest 61,2% influenced by other factors outside the research. Then the T-test results show that the TikTok marketing variable has a significant positive effect onbrand awareness And brand image.The results of this study prove that the theory Brand Equity relevant to explain how marketing strategies through TikTok are able to strengthen brand awareness and brand image among TikTok followers @ecinos.id.